Correlações fenotípicas e genotípicas, adaptabilidade e estabilidade em genótipos de soja - Romanato, Fernanda Neves (2013)
The selection and recommendation of superior genotypes are basic activities of a breeding program. The knowledge of phenotypic and genotypic contributes to defining best selection strategies. Obtaining genotypes with high grain yield is the main goal of soybean breeding programs. The genotype x environment interaction (G x E) constitutes one of the major difficulties during cultivar recommendation. It is known that the interaction G x A can be reduced by using environment-specific cultivars or wide adaptability and high stability. The objective of this work was to study the adaptability and stability of 25 soybean lines and phenotypic and genotypic correlation of 24 soybean lines, all from the soybean breeding program at the Federal University of Uberlândia. The study of adaptability and stability was conducted with 30 genotypes, 25 strains and five witnesses (BRSMG Garantia UFUS Impacta, UFUS Xavante UFUS Milionária, M-Soy 8914) in a randomized complete block design with three replications in three seasons sowing (November 2006, November 2007 and November 2008) in the city of Campo Alegre de Goiás-GO. In each plot was determined the productivity of grains. For the study on adaptability and stability, we used the methods of Eberhart and Russell (1966), Lin and Binns (1988) modified by Carneiro (1998) and Centroid (ROCHA, 2005). The average grain yield was 3104.201 kg ha-1.As UFUS strains 6, 21 and UFUS-cultivars UFUS Impacta and UFUS Xavante stood out to have high average yield, wide adaptation and high stability for all methods studied. To study the correlations between agronomic characters of soybean, an experiment was conducted at Capim Branco Farm, Uberlândia, MG. On May 24, 2012, it was done a conventional sowing of 24 strains derived from the soybean breeding program UFUS and 3 cultivars (BR/MG46-Conquista, UFUS UFUS Carajás and UFUS Guarani). It was evaluated the characters, the days to flowering and maturity respectively; plant height at flowering and maturity, number of nodes on the main stem at flowering and maturity respectively, first pod height, grain yield per plant, total number of pods per plant, and average weight of a hundred grains. Statistical analyzes were performed by the computer program in genetics and statistics GENES (Cruz, 2009). For the determination coefficient, the highest values were found for average weight of hundred grains (95.01%) and the lowest for the total number of pods (36.54%). The characters mean weight of one hundred grains and total number of pods were positively correlated with grain yield and thus can be used as an indirect selection criterion.